2017
DOI: 10.5820/aian.2402.2017.1
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Examination of the Center for Epidemiologic Studies Depression Scale with Older American Indians: The Native Elder Care Study

Abstract: We sought to examine behavioral health indicators for an early adolescent population of American Indians/Alaska Natives (AI/AN) within an urban setting in Washington State. We conducted secondary data analyses from a randomized clinical trial implemented in local middle schools that compared AI/ANs (n = 43), non-Hispanic Whites (n = 620), and other racial/ethnic minority youth (n = 527) across a variety of behavioral health risks. AI/AN youth reported significantly more depressive symptoms than other racial/et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Thus, age and education tend to moderate depressive symptoms in variable ways, depending on the setting and sample. Across studies, a high level of social support and self-efficacy (Schure and Goins, 2017) was found to be a buffer (protective factor) against depressive symptoms (Roh et al, 2015;C¸ayır et al, 2017;Schure and Goins, 2017).…”
Section: Depressionmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, age and education tend to moderate depressive symptoms in variable ways, depending on the setting and sample. Across studies, a high level of social support and self-efficacy (Schure and Goins, 2017) was found to be a buffer (protective factor) against depressive symptoms (Roh et al, 2015;C¸ayır et al, 2017;Schure and Goins, 2017).…”
Section: Depressionmentioning
confidence: 96%
“…We use the terminology AI/ANs to denote research specifically conducted with these groups (excluding Native Hawaiians). In addition, older AI/ANs have been found to have higher rates of depressive symptomatology, with one study finding 13.24 per cent of elders having clinical depression (Schure and Goins, 2017). On the basis of limited research available on Native Hawaiians, rates of depression range from 8 to 12.2 per cent (Salvail and Smith, 2007).…”
Section: Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the 20-item and 12-item CES-D scales were tested in a sample of older AI adults in the Southeast region of the U.S. (Schure & Goins, 2017). While their findings determined high internal reliability and concurrent validity of the full 20-item and the 12-item CES-D scale scores, the 12-item scale resulted in a 1-factor model, as opposed to a 3-factor model (Chapleski et al, 1997).…”
mentioning
confidence: 99%
“…The scale is reliable and valid in diverse populations (Radloff, 1977) and demonstrates good internal consistency with both American Indian youth (Manson, Ackerson, Dick, Baron, & Fleming, 1990) and adults (Somervell et al, 1993). The Cronbach's alpha for the Elder Care Study sample is 0.87 and showed good convergent and divergent validity (Schure & Goins, 2017). The cut-point score most commonly used to indicate those at risk for clinically significant depression is ≥16, but a lower cut-point of 12 may be more appropriate for older adults (Lewinsohn, Seeley, Roberts, & Allen, 1997).…”
Section: Methodsmentioning
confidence: 99%